The diversity of fungi consortium isolated from polluted soil for degrading petroleum hydrocarbon (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Novianty R, Saryono, Awaluddin A, Pratiwi NW, Hidayah A, Juliantari E. 2021. The diversity of fungi consortium isolated from polluted soil for degrading petroleum hydrocarbon. Biodiversitas 22: 5077-5084. One of the major problems in the petroleum industry nowadays is crude oil spills. Riau Province, Sumatra is one of the largest oil producers in Indonesia. Accidental releases of petroleum products are of particular concern to the environment. The process of drilling and refining petroleum generates a large amount of oil sludge. One of the effective technologies used in the waste degradation process is bioremediation using certain microorganisms. The prime objective of the current research was to evaluate the efficiency of fungi consortiums in crude oil degradation in Bumi Siak Pusako-Pertamina Hulu, Indonesia. There are three potential fungi isolates as petroleum hydrocarbon degradation agents with four consortium variations. The parameter values of Optical Density (OD), pH, and diluted CO2 were measured on 0, 4, 8, and 16 days. To evaluate the fungal biodegradation activity using Gas Chromatography-Mass Spectrometry (GC-MS). The result showed that consortium II (KF II) has the highest potential to degrade petroleum hydrocarbon (50.61%). The visual GC-MS examination confirmed a decrease in the peak area for eight hydrocarbon compounds, indicating the efficiency of the fungi in the oil decomposition and dismantling of hydrocarbons. Our findings may provide new information on native fungal resources from chronically contaminated terrestrial environments, and will be useful for petroleum-contaminated bioremediation and other industrial applications.
Keywords: Biodegradation, crude oil, fungi consortiums, Petroleum Contaminants